Mother's Knowledge In The First Management Of Child Fever in North Demangan - Eka Sarofah Ningsih; Mise Mise (Universitas STRADA Indonesia, 2020)
Fever is the body's normal response to infection. Infection is a condition where microorganisms enter the body, which can be viruses, bacteria, parasites, or fungi. Fever in children is generally caused by a viral infection (Setiawati, 2010). This research is a quantitative research with analytic research type and with cross sectional approach method. with a sample size of 50 respondents. Knowledge can be influenced by educational factors, where it is hoped that with higher education the knowledge will be wider. Respondents' understanding of how to determine fever treatment was good enough. Almost all respondents (80%) are aware that measuring body temperature using a thermometer is the most accurate way to find out a child's body temperature. Measuring body temperature using a thermometer is more accurate than using hand touching because hand touch is subjective and does not accurately assess body temperature